The Gunditjmara land justice story - Weir, Jessica K.; Australian Institute of Aboriginal and Torres Strait Islander Studies. Native Title Research Unit. (Acton, A.C.T. : Native Title Research Unit, Australian Institute for Aboriginal and Torres Strait Islander Studies, 2009)
Tells the story of the Gunditjmara's fight for their land from the early 1800s to the consent determination for their country, celebrated in March 2007; contact history of the area including the Eumerella Wars; setting up of Lake Condah Mission; discusses the legal significance of the court case undertaken by Sandra Onus and Christine Frankland against Alcoa, which resulted in the mission land being handed back to the Gunditjmara; how native title for the area was negotiated; establishment of the Gunditj Mirring Traditional Owners Corporation; Tyrendarra Indigenous Protected Area; Lake Condah Sustainable Development Project and the work towards the re-flooding of Lake Condah.
Includes bibliographical references (p. 40)
Digital content preserved
Keywords: Native title (Australia) -- Victoria; Aboriginal Australians -- Land tenure -- Victoria; Gunditjmara (Australian people); Aboriginal Australians -- Victoria -- History; Land rights - Land acquisition; Gunditjmara / Gurndidy / Dhaurwurd-Wurrung people (S20) (Vic SJ54-11); Environment - Conservation; Land rights; Native title - Determinations - Victoria; Indigenous knowledge - Ecology; Animals - Fish - Eels; Environment - Lakes and rivers; Budj Bim / Mount Eccles (SW Vic SJ54-07); Tae Rak / Lake Condah (W Vic SJ54-11); Deen Maar / Lady Julia Percy Island (W Vic SJ54-11)